Point of care ultrasonography in the pediatric emergency department - Julien Le Coz; Silvia Orlandini; Luigi Titomanlio; Victoria Elisa Rinaldi (BMC, 2018)
Abstract Importance Point-of-care ultrasonography (POCUS) allows to obtain real-time images to correlate with the patient's presenting signs and symptoms. It can be used by various specialties and may be broadly divided into diagnostic and procedural applications. Objective We aimed at reviewing current knowledge on the use of POCUS in Pediatric Emergency Departments (PEDs). Findings US diagnostic capacity in paediatric patients with suspected pneumonia has been studied and debated whereas literature regarding the usefulness of point-of-care echocardiography in the pediatric setting is still limited. Similarly, Focused Assessment with Sonography for Trauma (FAST) has become a standard procedure in adult emergency medicine but it is still not well codified in the pediatric practice. Concerning procedural applications of POCUS we identified 4 main groups: peripheral vascular access, bladder catheterizations, identification and drainage of abnormal fluid collections and foreign body identification. Conclusions and relevance Bedside emergency ultrasound is routinely used by adult emergency physicians and in the last 10 years its application is recognized and applied in PED. Pediatric emergency physicians are encouraged to familiarize with POCUS as it is a safe technology and can be extremely helpful in performing diagnosis, managing critical situations and guiding procedures, which results in globally improving pediatric patients care.